Shifting the Way the Public Forms Religious Understanding in the Era of Digital Disruption - Imam Hidayat; Hamid Samiaji, Mukhamad (Lembaga Kajian Nusantara Raya (LK Nura), 2025)
The era of digital disruption has brought a major transformation in the way people access, understand, and form religious beliefs. Advances in information and communication technology, particularly through the internet and social media, have created new spaces that challenge conventional religious authority structures. This article aims to analyze how digital disruption changes the pattern of religious formation among the public, focusing on changes in the source of authority, religious learning mechanisms, and the dynamics of virtual communities. This study uses a qualitative-descriptive approach with literature studies and digital observations. The results of the study show that there is a shift in religious authority from formal institutions to religious figures who are active on social media, there is a tendency for fragmentation and polarization in religious discourse, the emergence of an economic religious content encourages the commodification of religion, and the weak digital literacy of the community increases the potential for the spread of false, intolerant, or extreme religious information. These findings confirm the need for adaptive strategies for religious institutions and the improvement of people's religious digital literacy.